Role of Astrocyte in Cortical Spreading Depression: A Quantitative Model of Neuron-Astrocyte Network (Communications in Computational Physics, 2018)
Cortical spreading depression (CSD) involves depolarization of neurons andastrocytes due principally to a large increase in extracellular potassium. CSD is alsoaccompanied by large increases in extracellular ATP and is blocked by glutamate N-methyl-D-aspartate(NMDA) receptor antagonists. In a previous study, we used a neuronalmodel to investigate the instigation of CSD and propagation of CSD wave byincreasing extracellular potassium. In this paper, we extend that model by constructinga neuron-astrocyte network and incorporating the effects of ATP via the coupledbiochemical pathways involving glutamate and NMDA currents. We show that boththe electrical current stimuli and the local elevation in the extracellular ATP or glutamateconcentration can lead to CSD in the coupled neuron-astrocyte model, whileATP or glutamate increase fails to induce CSD when the glutamate NMDA channelsare blocked. These results can explain both the potassium theory postulated by Grafsteinand glutamate theory by Van Harreveld. Our model showed extracellular potassiumplays the key role in CSD instigation and propagation, and glutamate is a keycompound mediating CSD by activating NMDA channels through neuron-astrocyteinteractive.
Keywords: Cortical spreading depression; ion transport; porous media; partial differential equations; finite difference solutions.